Comparison Study of Genotoxic Action of High- Versus Very Low Dose-Rate γ-Irradiation - A. N. Osipov; D. Y. Klokov; A. L. Elakov; O. M. Rozanova; S. I. Zaichkina; G. F. Aptikaeva; A. Kh. Akhmadieva (SAGE Publishing, 2004)
The aim of the present study was to compare genotoxicity induced by high- versus very low dose-rate exposure of mice to γ-radiation within a dose range of 5 to 61 cGy using the single-cell gel electrophoresis (comet) assay and the micronucleus test. CBA/lac male mice were irradiated at a dose rate of 28.2 Gy/h (high dose rate) or 0.07 mGy/h (very low dose rate). The comet assay study on spleen lymphocytes showed that very low dose-rate irradiation resulted in a statistically significant increase in nucleoid relaxation (DNA breaks), starting from a dose of 20 cGy. Further prolongation of exposure time and, hence, increase of a total dose did not, however, lead to further increase in the extent of nucleoid relaxation. Doses of 20 and 61 cGy were equal in inducing DNA breaks in mouse spleen lymphocytes as assayed by the comet assay. Of note, the level of DNA damage by 20-61 cGy doses of chronic irradiation (0.07 mGy/h) was similar to that an induced by an acute (28.2 Gy/h) dose of 14 cGy. The bone marrow micronucleus test revealed that an increase in polychromatic erythrocytes with micronuclei over a background level was induced by very low-level γ-irradiation with a dose of 61 cGy only, with the extent of the cytogenetic effect being similar to that of 10 cGy high-dose-rate exposure. In summary, presented results support the hypothesis of the nonlinear threshold nature of mutagenic action of chronic low dose-rate irradiation.